Dataset on passenger acceptance during autonomous ferry public trials: Questionnaires and interviews - Veitch, Erik; Alsos, Ole Andreas; SAGHAFIAN, MINA; Petermann, Felix-Marcel; Sitompul, Taufik Akbar; Park, Jooyoung (Data in Brief, 2024)
This paper presents a dataset from the first public trial of an urban autonomous passenger ferry. The dataset contains questionnaires designed to assess passenger acceptance in terms of perceived safety, trustworthiness, and reliability. Questionnaires and their responses are paired samples collected before and after use (N = 884). The dataset also contains transcripts of semi-structured interviews on the themes of perceived safety, trustworthiness, and reliability (N = 25). The public trial was held in Trondheim, Norway, during the period September-October 2022. The autonomous ferry used in the trial was the “milliAmpere2,” which is owned and operated by the Norwegian University of Science and Technology (NTNU). The data represents a state-of-the-art data collection effort owing to on-site data collection immediately before and after interactions with an Autonomous Vehicle (AV) in a public transportation context. The dataset is suitable for producing quantitative and qualitative analyses and for developing indicators of technology acceptance and related social phenomena regarding AVs, either in the maritime context or beyond. This research was funded by NTNU (Pro-rector for Innovation; Strategic Research Areas for NTNU Oceans, NTNU Digital, NTNU Energy, and NTNU Sustainability), as well as by Trondheim Municipality and the Norwegian Research Council (the latter through the projects SFI AutoShip and MIDAS: grant numbers 309230 and 331921, respectively). In addition, the public trial was supported by Trondheim Harbor and The Coastal Federation (Kystlaget). We gratefully acknowledge the employees at Zeabuz AS for their contributions to the trial operations and the research assistants at NTNU for their contributions to data collection. We also acknowledge the safety hosts from Torghatten AS, representatives from the Norwegian Maritime Authority, as well as Egil Eide and Morten Breivik for their roles in organizing the public trials.